Atmospheric sink of β-ocimene and camphene initiated by Cl atoms: kinetics and products at NOx free-air. Issue 48 (31st July 2018) - Gaona-Colmán, Elizabeth; Blanco, María B.; Barnes, Ian; Wiesen, Peter; Teruel, Mariano A.
Abstract : Rate coefficients for the gas-phase reactions of Cl atoms with β-ocimene and camphene were determined to be (in units of 10 −10 cm 3 per molecule per s) 5.5 ± 0.7 and 3.3 ± 0.4, respectively. Abstract : Rate coefficients for the gas-phase reactions of Cl atoms with β-ocimene and camphene were determined to be (in units of 10 −10 cm 3 per molecule per s) 5.5 ± 0.7 and 3.3 ± 0.4, respectively. The experiments were performed by the relative technique in an environmental chamber with FTIR detection of the reactants at 298 K and 760 torr. Product identification experiments were carried out by gas chromatography with mass spectrometry detection (GC-MS) using the solid-phase microextraction (SPME) method employing on-fiber carbonyl compound derivatization with o -(2, 3, 4, 5, 6-pentafluorobenzyl) hydroxylamine hydrochloride. An analysis of the available rates of addition of Cl atoms and OH radicals to the double bond of alkenes and cyclic and acyclic terpenes with a conjugated double bond at 298 K is presented. The atmospheric persistence of these compounds was calculated taking into account the measured rate coefficients. In addition, tropospheric chemical mechanisms for the title reactions are postulated.